1999
DOI: 10.1046/j.1365-2443.1999.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe osteopetrosis, defective interleukin‐1 signalling and lymph node organogenesis in TRAF6‐deficient mice

Abstract: Background: TRAF6, a member of the tumour necrosis factor receptor-associated factor family, was first identified as a transducer of CD40 and interleukin-1 receptor (IL-1R) signals based on the interaction of TRAF6 with the cytoplasmic tail of CD40 and with the IL-1R associated kinase in vitro. However, the functions of TRAF6 in vivo remain unidentified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
457
3
5

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 600 publications
(479 citation statements)
references
References 44 publications
9
457
3
5
Order By: Relevance
“…Traf6 has been shown to bind directly to Troy, and this interaction, therefore, could take place in tooth germ epithelium (Naito et al, 2002). Traf6 mutant mice exhibit an HED skin and hair phenotype and die between 17 and 19 days postnatal (Naito et al, 1999(Naito et al, , 2002. To determine whether these mice had a tooth phenotype, we examined sections of teeth from newborn mutants.…”
Section: Tooth Phenotype In Traf6 Mutant Micementioning
confidence: 99%
See 2 more Smart Citations
“…Traf6 has been shown to bind directly to Troy, and this interaction, therefore, could take place in tooth germ epithelium (Naito et al, 2002). Traf6 mutant mice exhibit an HED skin and hair phenotype and die between 17 and 19 days postnatal (Naito et al, 1999(Naito et al, , 2002. To determine whether these mice had a tooth phenotype, we examined sections of teeth from newborn mutants.…”
Section: Tooth Phenotype In Traf6 Mutant Micementioning
confidence: 99%
“…Traf6 mutant mice were produced as described by Naito et al (1999). Crinkled mice were produced as described by Headon et al (2001).…”
Section: Experimental Procedures Preparation Of Mutant and Wild-type mentioning
confidence: 99%
See 1 more Smart Citation
“…(4,5) Numerous studies have shown that the receptor activator of NF-kB (RANK) signaling pathway is crucial for the differentiation and activation of osteoclasts. (6)(7)(8) Therefore, the amount of RANK ligand (RANKL) on the osteoblastic cell surface, where RANKL binds to RANK through cell-to-cell contact and triggers downstream signaling in osteoclast precursors, is considered to determine the magnitude of the signal input and the degree of osteoclastogenesis. (9,10) Previously, we have shown that most of the newly synthesized RANKL is transferred from the Golgi apparatus to the lysosomal storage compartment via the route involving vacuolar protein sorting 33a (Vps33a) in osteoblastic cells.…”
Section: Introductionmentioning
confidence: 99%
“…(5) Numerous studies, including detailed in vitro analyses and in vivo genetic investigations, have revealed that the receptor activator of the NF-kB (RANK) signaling is crucial for differentiation and activation of osteoclasts. (6)(7)(8) Most previous studies have focused on the total amount of RANK ligand (RANKL) expressed in whole osteoblastic cells, including studies focused on transcriptional regulation of RANKL. (9)(10)(11) However, only RANKL molecules expressed at the cell surface actually can bind to RANK, which is located at the cell surface of osteoclast precursor cells.…”
Section: Introductionmentioning
confidence: 99%